Use of the Six Sigma by the 500 Largent Companies in Portugal - Conceição, A.; Major, M. (RBGN - Revista Brasileira de Gestão de Negócios, 2011)
The Six Sigma had its genesis in big industrial companies that have implemented it as a tool for reducing defects. The initial success encouraged its application in other areas and we see today successful implementation in other sectors such as services, and within their own organizations in other areas beyond production, setting; this has contributed to Six Sigma being recognized as a new management model. In order to determine the extent to which Six Sigma is present in Portuguese companies, a questionnaire has been designed to target the 500 largest, non-financial companies, operating in Portugal. From the analysis of the results, we can conclude that top management support and level of involvement of employees in developing and implementing Six Sigma projects are perceived as critical factors in successful implementations. In terms of impact on the organization's adoption of Six Sigma, research conducted showed that after its implementation there have been gains in productivity and, in general, a greater satisfaction of external customers. Furthermore, findings evidenced that Six Sigma still has little expression in the large Portuguese companies, although there is an interest in this approach, only superseded by ISO 9001 and the Balanced Scorecard approach.